Association between physical activity and menstrual cycle disorders in young athletes - Passoni, P.; Inzoli, A.; De Ponti, E.; Polizzi, S.; Ceccherelli, A.; Fantauzzi, M.; Procaccianti, C.; Cattoni, A.; Villa, S.; Riva, A.; Righetti, S.; Landoni, F.; et al. (International Journal of Sports Medicine, 2024)
Our study aims to evaluate clinical predictors of menstrual cycle disorders in female athletes who compete in running disciplines. This is a prospective observational study. Women were recruited between January and May 2022. Fifty-three patients were enrolled and completed a questionnaire about menstrual cycle, physical activity, and food habit characteristics. Of the women in our population, 39.6% had menstrual irregularities and reported a significantly higher number of kilometers run per week (67 vs. 35, p:0.02). The number of kilometers run per week was associated with menstrual irregularities (for 10 km, OR 1.35; IC95% 1.05-1.73; p: 0.02) after adjusting for BMI, age, level of sport and caloric intake. The variable of "km run per week" appeared as a diagnostic indicator of irregular menstrual cycle with statistical significance (AUC ROC curve 0.71, IC95% 0.54-0.86, p-value=0.01) and the cut-off of 65 km run per week is a good indicator of the presence of irregular menstrual cycle (sensitivity (SE) and specificity (SP) of 55% and 81.48%). Menstrual cycle disorders are very frequent in female athletes, and the variable of km run per week may play a role in screening endurance athletes at high risk for these disorders.